2023
DOI: 10.3390/v15020515
|View full text |Cite
|
Sign up to set email alerts
|

The Synergy of Chicken Anemia Virus and Gyrovirus Homsa 1 in Chickens

Abstract: Chicken anemia virus (CAV) and Gyrovirus homsa 1 (GyH1) are members of the Gyrovirus genus. The two viruses cause similar clinical manifestations in chickens, aplastic anemia and immunosuppression. Our previous investigation displays that CAV and GyH1 often co-infect chickens. However, whether they have synergistic pathogenicity in chickens remains elusive. Here, we established a co-infection model of CAV and GyH1 in specific pathogen-free (SPF) chickens to explore the synergy between CAV and GyH1. We discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In particular, GyH1 mono-infection experiments showed that GyH1 virus shedding began at 14 days post-infection, peaked at 21 days post-infection, and began to decrease at 28 days post-infection. Additionally, immune organ dynamic monitoring experiments and erythrocyte testing experiments have further validated our results [14,15,19].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In particular, GyH1 mono-infection experiments showed that GyH1 virus shedding began at 14 days post-infection, peaked at 21 days post-infection, and began to decrease at 28 days post-infection. Additionally, immune organ dynamic monitoring experiments and erythrocyte testing experiments have further validated our results [14,15,19].…”
Section: Discussionsupporting
confidence: 72%
“…Co–infection of GyH1 with other gyroviruses, e.g., gyrovirus galga1 (GyG1) and CAV, occurs frequently. Importantly, GyH1 co–infection with CAV leads to higher mortality and more widespread lymphocyte apoptosis [ 19 ], which increases the risk posed and makes prevention and control more difficult. Specifically, epidemiology investigation suggests that GyH1 is widespread in China, which is consistent with our findings [ 17 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, other circoviruses have been reported, and several species have been shown to be pathogenic to poultry ( Truchado et al, 2019 ; Feher et al, 2022 ; Yan et al, 2023 ). Yang et al found that GyH1 and CAV synergistically promote immunosuppression, pathogenicity, and viral replication in co-infected chicken, highlighting the interaction between CAV and GyH1 in the disease process and increasing potential health risk in the poultry breeding industry ( Yang et al, 2023 ). As an early discovered and reported avian gyroviruses, GyVg1 should draw more attention to its public health and safety hazards, and as a member of the gyroviruses, GyVg1 also provides valuable research materials for human studies to reveal the life cycle of gyroviruses.…”
Section: Discussionmentioning
confidence: 99%